The impact of governance, innovation, and macroeconomic factors on renewable energy generation in ASEAN: A Bayesian approach - Saizal Pinjaman; Mcxin Tee; Wong Sing Yun; Sarimah Surianshah; Haryo Kuncoro; Liangyan Lu; Zhu Ling (Taylor & Francis Online, 2025)
This study investigates the influence of governance, innovation, and macroeconomic factors on renewable energy generation in ASEAN (2002–2022). It examines how eco- nomic growth, education, governance quality, capital formation, oil rents, foreign direct investment (FDI), and innovation influence renewable energy generation. By employing Bayesian regression, the results reveal that higher economic growth boosts renewable energy generation, while governance and capital formation negatively impact it. FDI and innovation also negatively influence renewable energy generation, indicating gaps in attracting FDI and translating innovation into practice. Policymakers need to promote equitable wealth distribution and enhance governance frameworks. The results also emphasize the importance of targeted policies to promote sustainable energy development by redirecting investments towards green sectors and utilizing oil rents for renewable energy projects. Additionally, improving intellectual property protection and providing support for small enterprises in the renewable energy sector enhance the practical application of innovations. These strategies are crucial for advancing renewable energy development in ASEAN, contributing to a sustainable energy future.